State of The Art Review: Building Computational Thinking on Science Education (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
Industrial Revolution 4.0 requires individuals to have the ability in the field of technology and use it to solve existing problems. Computational Thinking (CT) is one of the skills needed in dealing with technological developments through a problem-solving process. Many research developments in the field of CT have been carried out, but the theoretical studies presented are still limited to the ability in solving problems using a computer. Whereas in its development, CT theory must be adapted to the scope and purpose of building it. Based on that, new research is needed which aims to test and analyze the truth of these findings and examine the stages of building appropriate CT for science students with state-of-the-art review method. By taking a specific scope that has not been studied by many researchers, namely science education, it is found that CT is the ability in dividing a problem into sub-steps, carry out deeper investigations, analyze and criticize and test the truth of something so that the right solution is obtained. This definition is more specific than the definition of CT in theory because it is adapted to the characteristics of science. Whereas from a state-of-the-art review of the stages of building CT, it was found that the stages of task decomposition, abstraction, generalization, data structures and algorithms were considered to optimalize the CT construction for science students. It is because students could identify tasks or problems and divide the problem into small parts at the task decomposition stage. Therefore, they can be completed one by one.